2023
DOI: 10.3102/10769986231160668
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Primary Students’ Reading Progression: Is Cognitive Diagnostic Computerized Adaptive Testing the Way Forward?

Abstract: Cognitive diagnostic computerized adaptive testing (CD-CAT) is a cutting-edge technology in educational measurement that targets at providing feedback on examinees’ strengths and weaknesses while increasing test accuracy and efficiency. To date, most CD-CAT studies have made methodological progress under simulated conditions, but little has applied CD-CAT to real educational assessment. The present study developed a Chinese reading comprehension item bank tapping into six validated reading attributes, with 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…That is, we do not assume any hierarchical or directional relationship among the attributes. However, as noted by Rupp et al (2010), the unstructured specification is unlikely to reflect observed data in educational contexts where hierarchical structures arise naturally (e.g., skills build on prerequisite skills)-for instance, when assessments are developed based on learning progressions, trajectories, or maps (e.g., Li et al, 2023;Yuan et al, 2022). As an example, Figure 2 shows a linear hierarchy where attribute 𝛼 𝐽 is mastered before 𝛼 𝐾 , which in turn must be mastered before 𝛼 𝐿 .…”
Section: Assessing Attribute Dependenciesmentioning
confidence: 99%
“…That is, we do not assume any hierarchical or directional relationship among the attributes. However, as noted by Rupp et al (2010), the unstructured specification is unlikely to reflect observed data in educational contexts where hierarchical structures arise naturally (e.g., skills build on prerequisite skills)-for instance, when assessments are developed based on learning progressions, trajectories, or maps (e.g., Li et al, 2023;Yuan et al, 2022). As an example, Figure 2 shows a linear hierarchy where attribute 𝛼 𝐽 is mastered before 𝛼 𝐾 , which in turn must be mastered before 𝛼 𝐿 .…”
Section: Assessing Attribute Dependenciesmentioning
confidence: 99%
“…Chen and Wang (2023) introduce methods for inferring the underlying graphical structure of student skills to infer the nature of the hierarchical structure of skill mastery, which is a central concern for designing learning interventions. Li et al (2023) demonstrate the utility of deploying diagnostic models in computerized adaptive testing (CAT) in an application involving elementary students Chinese reading comprehension. The second collection of papers are grounded in the factor analytic tradition and provide novel extensions and applications to identify and detect beneficial educational interventions.…”
mentioning
confidence: 99%